2012
DOI: 10.5999/aps.2012.39.4.404
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Fingertip Amputation in Adults by Palmar Pocketing of the Amputated Part

Abstract: BackgroundFirst suggested by Brent in 1979, the pocket principle is an alternative method for patients for whom a microsurgical replantation is not feasible. We report the successful results of a modified palmar pocket method in adults.MethodsBetween 2004 and 2008, we treated 10 patients by nonmicrosurgical replantation using palmar pocketing. All patients were adults who sustained a complete fingertip amputation from the tip to lunula in a digits. In all of these patients, the amputation occurred due to a cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Palmar digital veins only exist in the nger pulp or the slant ulnar side and the outer diameter is wee. According to this feature, the Tamai partition method divides the ngertip into two zones, the Zone I: the lunula (methyl) to the nger end; the Zone II: the distal interphalangeal joint to the lunula (methyl) [22]. All of our cases were belonged to Zone I.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Palmar digital veins only exist in the nger pulp or the slant ulnar side and the outer diameter is wee. According to this feature, the Tamai partition method divides the ngertip into two zones, the Zone I: the lunula (methyl) to the nger end; the Zone II: the distal interphalangeal joint to the lunula (methyl) [22]. All of our cases were belonged to Zone I.…”
Section: Discussionmentioning
confidence: 97%
“…Many scholars have improved it and achieved satisfactory results in this technology. Like abdomen hypodermic embedding, some scholars used other nger [19] or palm [20] to foster the smaller amputated ngertip. All of them have their respective advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique has a higher rate of failure than other techniques, and this can eventually necessitate further surgery . Another method is known as palmar pocketing, wherein the amputated part is “pocketed” into palmar tissue . However, this method leads to hand stiffness because of the reconstructed finger being kept in a bent position for over 2–3 weeks, along with an extremely long period of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…The critical factor when utilizing bone and nail tissue as a graft for reconstruction is to choose a flap that is sufficiently vascular to nourish these grafts. Jung et al [2] reported that a subcutaneous pocket could provide extra blood supply for survival of the composite graft of the amputated fingertip by enlarging the area of vascular contact. Muneuchi et al [3] emphasized that the subcutaneous pocket technique be performed scrupulously for fingertip amputation across or proximal to the lunula because of the poor survival rate and the possibility of contracture of the digits or other proximal joints.…”
Section: Introductionmentioning
confidence: 99%